Animals and their people : connecting east and west in cultural animal studies - Barcz, Anna, 1979- (Human-animal studies, 2019)
Animals and Their People: Connecting East and West in Cultural Animal Studies, edited by Anna Barcz and Dorota Åāgodzka, provides a zoocentric insight into philosophical, artistic, and literary problems in Western, Anglo-American, and Central-Eastern European context. The contributors go beyond treating humans as the sole object of research and comprehension, and focus primarily on non-human animals. This book results from intellectual exchange between Polish and foreign researchers and highlights cultural perspective as an exciting language of animal representation. Animals and Their People aims to bridge the gap between Anglo-American and Central European human-animal studies.